The Use of “Think, Pair, Share” Technique in Teaching Reading Comprehension of Descriptive Text - Juventini, Valentina; Sumarni, Sumarni; Novita, Dewi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study investigated the effectiveness of the Think, Pair, Share technique in teaching reading comprehension of descriptive text to eighth-grade students at SMP Negeri 1 Simpang Dua in the academic year 2024/2025. This study uses pre-experimental research design, with the following steps: pre-test, treatment, and post-test. The sample of this research involved 42 students from the eighth grade of SMP Negeri 1 Simpang Dua selected by total random sampling. The tool of this research is a reading comprehension test. The finding showed a significant improvement in students’ scores, and it proved that the Think, Pair, Share technique was effective. Data analysis using paired t-tests showed the significant improvement in students’ reading comprehension abilities, with the t-test value of 10.53 was much higher than the critical t-table value of 1.684 (10.53 > 1.684). This indicates a significant difference between the pre-test and the post-test. Furthermore, the effect size was calculated and showed the value of 1.61; it can be consider that the “Think, Pair, Share” technique had a strong effect in teaching reading comprehension of descriptive text to eighth-grade students of SMP Negeri 1 Simpang Dua in the academic year 2024/2025. These findings suggest that the Think, Pair, Share technique is highly possible to be used as an alternative technique to teach reading comprehension of descriptive text to eighth-grade students of junior high school.